Forging a link between business strategy and business re-engineering - Edwards, Chris; Peppard, Joe (Cranfield University, 1994)
For many organisations the crucial issue in the strategy process is that of implementation. This is due in no small way to the distinction which is traditionally made between formulation and implementation and their treatment as sequential activities. The more recent conceptualisation of strategy, captured by the notion of core competencies, is blurring the distinction between formulation and implementation. This emerging 'behavioural perspective' of strategy focuses on the capabilities an organisation needs. Yet it still fails to address fully issues of implementation. In this paper, business reengineering is proposed as a natural ally of strategy. It is suggested that business reengineering can help bridge the gap between strategy formulation and implementation. In this context, business reengineering is seen as an approach which defines the business architecture enabling the organisation to focus more clearly on customer requirements.